Współczesna polska muzyka teatralna - Magdalena Figzał (Postscriptum Polonistyczne)
The article is an attempt to describe the function of music in contemporary Polish dramatic theatre. The author of the text refers to the art of Polish theatre directors and composers in order to show that music in dramatic theatre is not only an illustration or a signal. The article analyses the compositions that were written for particular performances, as well as borrowed compositions which are musical citations.